Development of high-performance broadband optical detector for cryogenic to elevated operating temperature. (May 2023) - Talib, Mohammad; Manzoor, Samrah; Sharma, Prachi; Tripathi, Nishant; Platonov, Vladimir; Pavelyev, Vladimir; Volkov, Valentyn S.; Arsenin, Aleksey V.; Syuy, Alexander V.; Hasan, P.M.Z.; Melaibari, Ammar A.; Mishra, Prabhash
Abstract: Development of broadband photodetectors for cryogenic and elevated temperature applications has been a major concern in space science and other radiation detection technologies. With this objective TiS2 -nanostructures were investigated for photodetection characteristics in the temperature range of −180 °C to 150 °C. The device was developed by depositing TiS2 -nanostructures amid gold-interdigitated electrodes by drop-casting technique. The photodetection performance was investigated for 617 nm and 850 nm LEDs as a function of power density and operating temperature. It is found that as-developed photodetector can operate in the solar spectrum from 375 nm to 1050 nm. The designed photodetector is capable of detecting photons at −180 °C temperature and 0.015 mW/cm 2 incident light power density with an ultra-low bias voltage (0.1 V). The operational temperature range can be further extended by optimizing the bias voltage. The device has excellent photodetection capabilities for from sub-zero temperature to elevated temperatures. The highest photocurrent of 45.22 nA is obtained at 617 nm and 0.1 V bias voltage, when the temperature is 0 °C and power density is 0.792 mW/cm 2, while the highest values for photoresponsivity (8.9 × 10 4 A/W), quantum efficiency (1.78 × 10 5 A/W nm), and detectivity (1.93 × 10 14 Jones) are found for 0.015 mW/cm 2 power density. Optimization of the Bias-voltage optimization further improves the device performance. At −120 °C operating temperature, the fastest response (response/recovery time∼0.099 s) and highest device ON/OFF ratio of the 'as-developed' photodetector are recorded.